From study abroad to study at home: Spontaneous neuronal activity predicts depressive symptoms in overseas students during the COVID-19 pandemic - Li, Tong; Du, Xiaoyu; Zhang, Xiang; Dong, Aiping; Yuan, Xianshun; Yu, Tianyi; Diao, Ruiyuan; Duan, Shuai; Shen, Zijian; Yuan, Letian; Wang, Ximing (Frontiers in Neuroscience, 2023)
The objective of this study was to evaluate symptoms of depression and anxiety as well as changes in spontaneous neuronal activity in college students studying abroad during the coronavirus 2019 (COVID-19) pandemic. We examined functional brain changes using resting-state functional magnetic resonance imaging (fMRI), the amplitude of low-frequency fluctuations (ALFF), and regional homogeneity (ReHo) in overseas students with enforced isolation due to the COVID-19 pandemic. Additionally, emotional assessments were administered to determine the severity of depression and anxiety. The questionnaire results showed that anxiety and depressive symptoms differed between overseas students (i.e., those attending an overseas college virtually) and local students (i.e., those attending a local college in person). The fMRI data revealed higher ALFF values in the bilateral superior medial frontal gyrus, bilateral pre-central gyrus, left insula, and left superior temporal gyrus as well as lower ALFF values in the bilateral paracentral lobule (supplementary motor area) in overseas students. Moreover, ReHo analysis also revealed significant differences between overseas students and local students. Compared with local students, overseas students showed significantly increased ReHo in the right inferior frontal and superior temporal gyri and decreased ReHo in the bilateral paracentral lobule, bilateral superior medial frontal gyrus (supplementary motor area), and bilateral pre-central gyrus. In addition, in overseas students, altered ReHo in the cluster including the left superior and medial frontal gyri, pre-central gyrus, and paracentral lobule was significantly positively correlated with Self-Rating Depression Scale scores. Thus, spontaneous brain activity in overseas students changed during the COVID-19 pandemic. This change in brain function might be related to depression and anxiety symptoms. These results suggest that mental health services are needed to decrease the risk of anxiety and depression among college students studying abroad during the COVID-19 pandemic.